The Implementation of the Picture and Picture Cooperative Learning Model to Improve Students’ Learning Activeness in Indonesian Language Learning - Salman Alfarisi; nur ilmi; Andi Fajar Asti (Journal of Primary Education Innovation and Research, 2025)
This study aims to improve the Indonesian language learning process and students’ learning activeness through the implementation of the Picture and Picture cooperative learning model in Grade V of UPTD SD Negeri 10 Parepare. This study used a qualitative approach with Classroom Action Research as the research design. The subjects of this study were one classroom teacher and 25 fifth-grade students, consisting of 11 male students and 14 female students. The research was conducted in two cycles, and each cycle consisted of planning, action, observation, and reflection stages. Data were collected through observation and documentation. The data were analyzed using data condensation, data presentation, and conclusion drawing. The results showed that the implementation of the Picture and Picture cooperative learning model improved both the learning process and students’ learning activeness. In Cycle I, teacher activity reached 67% and student activity reached 62%, both categorized as fair. Students’ learning activeness in Cycle I reached 50%, which was categorized as low. After improvements were made in Cycle II, teacher activity increased to 87% and student activity increased to 81%, both categorized as good. Students’ learning activeness also increased to 80%, which was categorized as high. These findings indicate that the Picture and Picture cooperative learning model can create a more active, visual, and meaningful learning process. Therefore, this model can be used as an alternative strategy to improve students’ learning activeness in Indonesian language learning at the elementary school level.